Uji Sitotoksik Hasil Fermentasi Kapang Endofit Buah Mahkota Dewa (Phaleria macrocarpa) terhadap Sel MCF-7 - Syarmalina Syarmalina; Wan Lely; Nazliah Laupa (Fakultas Farmasi Universitas Pancasila, 2007)
In the development of traditional medicine, there are great demands of medicinal plant. Meanwhile, those demands exceed the capacity of natural resource to provide the raw material. The solution for that problem that has been developed is by utilizing organism that live on plant tissue, which known as endophytic microbe. The preliminary Brine Shrimp Lethality Test based research on the polarity degree of supernatant extracts has proved that it has high toxic activity on Artemia salina Leach. Subsequent to that study, a research to examine in vitro cytotoxic effect of supernatant extract fermented from Mahkota Dewa fruit endophytic mould KVM/a and KIVM/b isolate on breast cancer cell has been conducted. Thin layer chromatographic test was performed to identify the patch pattern from each fraction of KVM/a and KIVM/b isolate. Furthermore, preparative thin layer chromatographic test was tested on MCF-7 cell by using neutral red method. The cytotoxic effect was determined based on ICs, value. The results confirm the cytotoxic test effect of semi polar fraction of both isolates on MCF-7 cell with the ICs, value of 36.26 ppm for KVM/a and 30.48 ppm for KIVM/b.